Upaya Meningkatkan Keterampilan Memainkan Akor Trinada Pokok Dengan Alat Musik Keybord Melalui Metode Pembelajaran Demonstrasi Pada Siswa Kelas IX G SMP Negeri 13 Magelang Semester Gasal Tahun Pelajaran 2022/2023 - Sutarsih, Denny (Science and Education Journal (SICEDU), 2024)
This research is classroom action research (PTK). Each cycle consists of three stages of activity, namely planning, implementing actions and observing, and reflecting. The subjects of this research were class 9G students at SMP Negeri 13 Magelang odd semester 2022-2023. There are 30 students in class 9 G, 14 boys and 16 girls. Data collection in this research used teacher and student activity observation sheets as well as written tests. The data analysis technique used is descriptive qualitative and descriptive quantitative with percentages. The results of the research show that the level of musical learning outcomes for the Basic Tritone Chord material for 9G Students of SMP N 13 Magelang after implementing Demonstration learning with a pilot in cycle I was 77.20 on average, after being carried out in cycle II the average was 83.50, which means it happened an increase of 6.3. Changes in behavior that occur in class 9G students at SMP N 13 Magelang in implementing learning using the pilot demonstration model include the following (a) students are more independent (b) students are more confident (c) students are more active (d) students are able to work together.